Pengaruh Leverage, Liquidity, Firm Size Dan Institutional Ownership Terhadap Dividend Policy - Djusnimar Zultilisna; Farida Titik Kristanti; Suriati Suriati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study is to reveal how leverage, liquidity, firm size and institutional ownership affect dividend policy in the property and real estate sector companies listed on the Indonesia Stock Exchange for the 2015-2021 period. The data applied in this study is secondary data obtained from annual reports or financial reports published on the Indonesia Stock Exchange website or company website. The sampling technique applied in this research is purposive sampling and obtained 6 companies from 79 research objects. The regression model applied is panel data regression. The results of the study reveal that there is a simultaneous influence of independent variables, namely leverage, liquidity, firm size and institutional ownership on dividend policy in property and real estate sector companies in 2015-2021. Partially, liquidity has a significant positive effect on dividend policy, while leverage, firm size and institutional ownership have no effect on dividend policy.